APPLICATION OF THE NON-RETROACTIVE PRINCIPLE BY JUDGES IN DISPUTES REGARDING TERMINATION OF EMPLOYMENT RELATIONS AFTER THE ELIGIBILITY OF THE JOB LAW AS A MANIFESTATION LEGAL CERTAINTY - Muhammad Mahendra Maskhur Sinaga; A. Harits Nu’man; Efik Yusdiansyah; Dini Dewi Heniarti (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study examines the application of the principle of non-retroactivity by judges in Indonesian industrial relations courts, specifically in cases of termination of employment (PHK) arising after the enactment of the Job Creation Law (UU Cipta Kerja). The research analyzes how courts balance the application of the new law with the legal principles protecting workers' rights and ensuring legal certainty. By examining relevant court decisions and legal doctrines, the study finds that judges generally adhere to the principle of non-retroactivity, applying the labor laws in effect at the time the cause of action arose (the PHK event). This adherence upholds constitutional rights and prevents unfair application of the Job Creation Law to pre-existing disputes. However, challenges remain in ensuring consistent application and interpretation, highlighting the need for clear guidelines and ongoing judicial education to promote legal certainty and fairness in industrial relations disputes.